Kekerasan dalam Pengasuhan Bagi Anak Pekerja Migran - Ngatma'in, Ngatma'in (Universitas Muhammadiyah Surabaya, 2024)
The research problem is how much violence in the care of migrant workers' children. The research method used is quantitative. The data in the study are in the form of numbers. The instrument used to collect data is a questionnaire. The research site is a community of migrant workers in Malaysia. Data collection was carried out on October 13, 2023. Analysis using descriptive statistics. The results of the analysis are presented in graphical form. The results showed that 82% of migrant workers' children had experienced violence in care. 54% of perpetrators of violence are mothers. 63% of the cause of violence is the condition of parents tired of working. 36% of forms of violence were pinching and anger. 59% of the impact of violence was trauma. keywords: child migrant workers, violence